Phytochemical Investigation and GC-MS analysis of Tribulus terrestris L. cultivated in Iraq - Amani Amer Tawfeeq; Tahany Amir Tawfeeq; Zahraa A.E Al Naqqash; ZIinah Alaa Kamal (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Tribulus terrestris L.,Gokshur in Sanskt, is an annual herbaceous, little prostrate, silky from the Zygophyllaceae family. It is found in extensive, arid, and scorching regions of India. is used in traditional folk medicines as an aphrodisiac, astringent, lithotriptic, diuretic, and urinary disinfectant. however, uneven, pinnae, elliptical leaves. Sprinkled, round, compressed, five-cornered, transverse partitioned carpel fruits with many seeds ripen in July. Pieces of the cylindrical-fibrous root are 7-18 cm and 0.3-0.7 cm wide. According to reported studies, the investigations indicated the presence of the saponins ;gitogenin, tigogenin, neogitogenin, hecogenin, and flavonoid tribuloside was kaempferol-3-glucoside. Furthermore, Tribulus terrestris plays a vital role in hepatotoxicity and is greatly reduced by Tribulus extracts. Similarly, T.terrestris plays a remarkable role in reducing the elevated level of serum glucose, triglycerides, VLDL, and cholesterol. This study aims to conduct a preliminary analysis of the phytochemicals of Tribulus leaves cultivated in Iraq and to determine the active constituent of the ethanolic extract of the leaves using Gc-Mass. Qualitative detection of herbal leaves in Iraqi soil, investigated by GC-MASS revealed important constituents. The funding shows a new compound; dihydrocoumarin and other major constituents neophytadiene and alpha-tocopherol.